Epistemologies of competence related knowledge - A system theoretical analysis - Uotila, Timo-Pekka (My University, 2010)
The purpose of this study is to examine the multiple views of knowledge and competence in organizations at different levels that cause indistinctness in competence management and to find out how competence related knowledge is achieved at different organizational levels. The objective is thus to bring underlying epistemologies of knowledge and competence into the academic discussion and further examine how they are expressed in practice. In the theoretical part of this study system theories and their use in management and organizational studies are examined. Open-system, connectivist and autopoietic approaches are clarified and their theoretical implications in organizational studies are presented. Also, the role of knowledge and its management in organizations is discussed, the vast field of knowledge management is presented and cognitivist, connectionist and autopoietic ways to conceptualize knowledge are considered. After a theoretical review a theoretical construct was formed and empirical findings were compared to it. This study was carried out in four Finnish companies and 11 persons from different organizational levels were interviewed in summer 2009. The methodology of this study is qualitative and empirical data was collected by using semi–structured interviews. In the analyzing phase the transcripts were carefully read, coded and further analyzed. As a result of this study different approaches to knowledge and competence could be found in different organizational levels. The supervisor level was found to achieve knowledge in everyday work in own unit. The HR level acted as a bridge builder in organizations and gathered knowledge through networking. The strategic management level created knowledge in strategy making process and focused on strategic competences. These findings were compared to the formed theoretical construct. Some distinctions could be made, autopoietic, connetionist and cognitivist characteristics were all found in the examined functions, but more research in the area is needed and thus future research suggestions are presented.
Keywords: Epistemology; knowledge; competence; system; autopoiesis; complexity; fi=Johtaminen ja organisaatiot|en=Management and Organization|